Spatio-temporal dynamics of early somite segmentation in the chicken embryo. - Ana Cristina Maia-Fernandes; Ana Martins-Jesus; Nísia Borralho-Martins; Tomás Pais-de-Azevedo; Ramiro Magno; Isabel Duarte; Raquel P Andrade (PLoS ONE, 2024)
During vertebrate embryo development, the body is progressively segmented along the anterior-posterior (A-P) axis early in development. The rate of somite formation is controlled by the somitogenesis embryo clock (EC), which was first described as gene expression oscillations of hairy1 (hes4) in the presomitic mesoderm of chick embryos with 15-20 somites. Here, the EC displays the same periodicity as somite formation, 90 min, whereas the posterior-most somites (44-52) only arise every 150 minutes, matched by a corresponding slower pace of the EC. Evidence suggests that the rostral-most somites are formed faster, however, their periodicity and the EC expression dynamics in these early stages are unknown. In this study, we used time-lapse imaging of chicken embryos from primitive streak to somitogenesis stages with high temporal resolution (3-minute intervals). We measured the length between the anterior-most and the last formed somitic clefts in each captured frame and developed a simple algorithm to automatically infer both the length and time of formation of each somite. We found that the occipital somites (up to somite 5) form at an average rate of 75 minutes, while somites 6 onwards are formed approximately every 90 minutes. We also assessed the expression dynamics of hairy1 using half-embryo explants cultured for different periods of time. This showed that EC hairy1 expression is highly dynamic prior to somitogenesis and assumes a clear oscillatory behaviour as the first somites are formed. Importantly, using ex ovo culture and live-imaging techniques, we showed that the hairy1 expression pattern recapitulates with the formation of each new pair of somites, indicating that somite segmentation is coupled with EC oscillations since the onset of somitogenesis.